2022
DOI: 10.1111/jfpp.17051
|View full text |Cite
|
Sign up to set email alerts
|

Development, characterization, and principal component analysis of fish bone‐based fortified refined wheat flour tortilla and its organoleptic attributes

Abstract: This study aimed to develop nano‐sized‐biogenic hydroxyapatite (HAp) from fishbone; followed by calcination at 850°C. The core part of the research “ultra‐sonication” was done following different levels of operating variables. Characterization of resulted HAp was done using different techniques. FTIR spectra confirmed PO43− peak at 1031.77 cm−1. As per the findings of atomic absorption spectroscopy (AAS) and particle size distribution (PSD), 128.04 ± 0.19 ppm calcium and 50–400 nm particle size were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
2
2
0
Order By: Relevance
“…These findings strongly support the potential of fish bone extracted nano‐biogenic HAp as an ingredient to increase calcium content in developed products reported by Liaqat et al. (2022).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…These findings strongly support the potential of fish bone extracted nano‐biogenic HAp as an ingredient to increase calcium content in developed products reported by Liaqat et al. (2022).…”
Section: Resultssupporting
confidence: 91%
“…In close agreement with these findings, the literature reported by Liaqat et al. (2022) suggested that Ca:P ratio was 1.69 in fish bone‐derived hydroxyapatite.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations